Supercontinuum generation in a nonlinear ultra-silicon-rich nitride waveguide - Yanmei Cao; Byoung-Uk Sohn; Hongwei Gao; Peng Xing; George F. R. Chen; Doris K. T. Ng; Dawn T. H. Tan (Scientific Reports, 2022)
Abstract Supercontinuum generation is demonstrated in a 3-mm-long ultra-silicon-rich nitride (USRN) waveguide by launching 500 fs pulses centered at 1555 nm with a pulse energy of 17 pJ. The generated supercontinuum is experimentally characterized to possess a high spectral coherence, with an average |g 12| exceeding 0.90 across the wavelength range of the coherence measurement (1260 nm to 1700 nm). Numerical simulations further indicate a high coherence over the full spectrum. The experimentally measured supercontinuum agrees well with the theoretical simulations based on the generalized nonlinear Schrödinger equation. The generated broadband spectra using 500 fs pulses possessing high spectral coherence provide a promising route for CMOS-compatible light sources for self-referencing applications, metrology, and imaging.